Improving the social performance of flash flood early warnings using mobile services. Issue 1 (9th February 2015) - Cumiskey, Lydia; Werner, Micha; Meijer, Karen; Fakhruddin, S.H.M.; Hassan, Ahmadul
Abstract : Purpose: – The purpose of this study is to provide recommendations for improving the social performance of warnings using mobile services in flash flood prone communities. A warning cannot be considered effective until it is received, understood and responded to by those at risk. This is defined as the social performance of warning communication techniques. Mobile services offer opportunities for improving this, particularly in Bangladesh, but have been underutilised. In this research, characteristics of the warning, mobile services and community are found to influence the social performance. Design/methodology/approach: – A framework on the factors affecting the social performance was developed and applied using data collected through interviews at the national and regional level along with focus-group discussions (FGDs) and key informant interviews at the local level in the Sunamganj District, Bangladesh. Findings: – The study demonstrated that mobile services are the preferred means of warning communication. Communities strongly preferred voice short messaging service (SMS) and interactive voice response (IVR) because of easier accessibility and understanding of the message. Text-based services [SMS and cell broadcasting service (CBS)] were still found to be acceptable. These should be simple, use symbols and refer to additional sources of information. Further recommendations include mixing push (e.g. SMS and CBS) and pull-based (e.g. IVR) mobile services, utilising local social networks, decentralising the dissemination process and raising awareness. Research limitations/implications: – A limited sample of interviews and FGDs were used. Practical implications: – Concrete recommendations are made for overcoming obstacles related to the effective use of mobiles services. Social implications: – The suggestions made can contribute to improving the social performance of flood early warning communication. Originality/value: – The conceptualisation of mobile services' contribution to social performance of flood warning and field-level application.